Selective bilateral hippocampal lesions after theophylline-induced status epilepticus causes a permanent amnesic syndrome - Kohl, Zacharias; Uyanik, G.; Lürding, R.; Schuierer, G.; Bogdahn, U.; Schröder, M.; Weidner, Norbert (Journal of clinical neuroscience, 2011)
Theophylline is known to increase the risk of epileptic seizures and might have a role in seizure-induced brain damage. We present a 55-year-old man who developed an amnesic syndrome after status epilepticus, caused by accidental theophylline intoxication. Imaging studies revealed acute, selective bilateral hippocampal damage, which corresponded to severe disturbances in bilateral temporal functions on neuropsychological testing. Three months later, the memory deficits persisted, while imaging exhibited bilateral atrophy of the hippocampus. Upon his long-term, 18-month follow-up, the patient demonstrated improvements in his daily living abilities, despite the persistence of bilateral temporal deficits. This report provides evidence that theophylline has the potential to provoke permanent seizure-induced neural damage, presumably via inhibition of adenosine receptors, and especially in vulnerable regions of the brain, such as the hippocampus.
Gesehen am 06.07.2022